Tinjauan Yuridis tentang Pertanggungjawaban Rumah Sakit Terhadap Pasien Korban Malpraktik Menurut Undang-Undang Nomor 36 Tahun 2009 Tentang Kesehatan - Qorina Khoirunisa; Evi Deliana; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Medical malpractice is negligence or inadequacy carried out by health personnel causing harm tothe patient either intentionally or unintentionally and can be accounted for. Indonesian health law does notyet have specific regulations regarding malpractice so that criminal liability in solving malpracticeproblems often becomes ambiguous. On the other hand, the Hospital as an institution with corporate legalstatus is in charge of providing facilities and health workers should also be responsible for negligencecaused by health workers who work in the hospital. So that the settlement of malpractice cases can be ashared responsibility between health workers and health care institutions. Legal certainty is needed todetermine more appropriate regulations so that they can be applied uniformly.Even though they do not have specific rules for dealing with malpractice, accountability can still betaken in criminal, civil and administrative law. The difficulty of proof from the side of the victim makes thesettlement of malpractice more often taken through civil law. Though most of the settlement of civilmalpractice often causes inequality and dissatisfaction for victims of malpractice patients. So that there isnot much that can be done by victims in dealing with these problems. And that is why the prosecution ofmalpractice cases is still very minimal.For administrative settlement, the Minister of Health formed MTKI (Indonesian Health Workers'Assembly) and MTKP (Provincial Health Workers' Assembly) which functioned as institutional supervisorsand health workers. One of the authorities of MTKI and MTKP is to issue a STR (Registration Certificate)and revoke it if the health worker or the institution concerned is proven to have committed a violation.Keywords: Accountability, Malpractice, Health Workers